… and justice for all – cost fairness in Volkswagen's product family. Issue 2 (8th May 2017) - Müller, David
Abstract : Purpose: Product families offer companies economic advantages in the development and the production stage while satisfying a wide range of customer needs. This concept generates economies of scale and scope, which lead to a significant cost reduction. The realization of product families by several autonomous firms highlights the problem of fair cost sharing. Despite broad agreement on fairness as a highly desired aim, in practice there is a lack of precise terms of operationalization. Therefore, the purpose of this paper is to use a game theoretical framework to achieve fair cost sharing. It is shown that the cooperative game solution ensures fairness and therefore should be accepted by all the partners. Design/methodology/approach: Therefore, this study uses a game theoretical framework to reach a fair cost sharing. All family members are modeled as players in a cost reduction game. Using a cooperative game lens allows the identification of fair cost shares. It is shown that cooperative game solution ensures fairness and therefore should be accepted by all partners. Findings: It is shown that the average cost assignment method is not fair and therefore not stable. Moreover, the authors show that the game theoretical solution ensures fairness and therefore will be accepted by all partners. Research limitations/implications: One main problem of the game theoretic solution concepts is the fact that the benefits of the PFD must be known for the various possible coalitions. By means of suitable forecasts, however, this can be avoided and is not a special problem of the game theoretical solution. The other two main problems are the assumption that the participating companies reach binding agreements ex ante, which are also met ex post, as well as the assumption that side payments between the participating companies are possible. Practical implications: It has been demonstrated that game theoretic instruments deliver a fair solution. With the calculated shares, all firms have an incentive to join the grand coalition what ensures a positive motivation and long-term stability. Originality/value: This paper's main contribution is the analysis of a real-life product family through the lens of cooperative game theory.